66.6k views
0 votes
Solve for x.
a. x + 5 = 6/x
b. x = 24/x - 5
c. x = 1/x

2 Answers

4 votes

Answer:

A.x+5=6x

Step 1:subtract 6x from both sides.

x+5-6x=6x-6x

-5x+5=0

Step 2:subtract 5 from both sides.

-5x+5-5=0-5

-5x=-5

Step 3:divide both by -5

-5x/5=-5/5

X=1

User Droplet
by
5.1k points
5 votes

Answer:

a. For equation
x+5=(6)/(x) value of x are 1 and -6.

b. For equation
x=(24)/(x)-5 value of x are 3 and -8

c. For equation
x=(1)/(x) value of x are -1 and 1.

Solution:

a)Given equation is
x+5=(6)/(x)

On cross multiplying we get,

x(x+5)=6


x^(2)+5 x-6=0

On splitting the middle term we get,


\begin{array}{l}{=x^(2)+6 x-x-6=0} \\ {=x(x+6)-1(x+6)=0} \\ {=(x-1)(x+6)=0}\end{array}

When x - 1 = 0 , x = 1

When x + 6 = 0 , x = -6

So two values of x which satisfies the given equation are 1 and -6.

b)Given equation is
x=(24)/(x)-5


\begin{array}{l}{=x * x=24-5 x} \\ {=x^(2)+5 x-24=0}\end{array}

On splitting the middle term we get


\begin{array}{l}{=x^(2)+8 x-3 x-24=0} \\ {=x(x+8)-3(x+8)=0} \\ {=(x-3)(x+8)=0}\end{array}

When x - 3 = 0 , x = 3

When x + 8 = 0 , x = -8

So two values of x which satisfies the given equation are 3 and -8.

c) Given equation is
x=(1)/(x)


\begin{array}{l}{=x * x=1} \\ {=x^(2)-1=0} \\ {=x^(2)-1^(2)=0}\end{array}

Using algebraic identity
a^(2)-b^(2)=(a-b)(a+b) we get

=(x-1)(x+1)=0

When x - 1 = 0 , x =1

When x + 1 = 0 , x = -1

So two values of x which satisfies the given equation are 1 and -1.

User Siavosh
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.